Atmospheric CO2 and its δ13C measurements from flask sampling at Lin'an regional background station in China. (September 2015) - Xia, Lingjun; Zhou, Lingxi; Tans, Pieter P.; Liu, Lixin; Zhang, Gen; Wang, Hongyang; Luan, Tian
Abstract: This study presents CO2 concentrations of air flask samples obtained at a regional background station Lin'an (LAN) in China from January 2009 to December 2013, as well as their stable isotope ratios (δ 13 C) from January 2011 to December 2013. Background data is selected to represent background characteristics of atmospheric CO2 and δ 13 C over Yangzte River Delta. The annual mean background CO2 concentrations vary from 395.0 ppm in 2009 to 407.6 ppm in 2013, with a growth rate of 2.8 ± 0.1 ppm yr −1 over the study period, which is higher than the global average level. The annual mean values of δ 13 C vary from −8.55‰ in 2011 to −8.73‰ in 2013, with a growth rate of −0.029 ± 0.010‰ yr −1 . Seasonal cycles of CO2 concentrations and δ 13 C are observed to be obvious at LAN. The minimum and maximum values of mean seasonal CO2 cycle appear in August and January, respectively, with the peak-to-peak amplitude of 19.4 ppm. The sign of δ 13 C seasonal cycle is opposite to that of CO2, and the peak-to-peak amplitude is 0.85‰. The isotopic signature of CO2 sources/sinks ( δ s ) is also discussed in this paper. The estimated δ s values for heating season (December–February) is −25.4‰ and for vegetative season is −21.3‰ (March–November) suggest the significant impact of fossil fuel combustions during winter heating season and biological activities during vegetative season. Highlights: Long-time records of background CO2 and δ 13 C are obtained at Lin'an in China. The annual CO2 and δ 13 C values are compared with other WMO/GAW background sites. CO2 and δ 13 C background values show positive and negative trends, respectively. Seasonal cycles and correlations of CO2 and δ 13 C background values are discussed.